Compressive strength measurements of hybrid dental composites treated with dry heat and light emitting diodes (LED) post cure treatment - Jenny Krisnawaty; Setiawan Natasasmita; Dudi Aripin (Universitas Padjadjaran, 2014)
Hybrid composites are mostly used on large cavities as restorative dental materials, whether it is used directly or indirectly. The mechanical properties of composite resin shall increase if it is treated with post cure treatment. The aim of this study is to evaluate compressive strength differences between dry heat and Light Emitting Diodes (LED) treatment on the hybrid dental composite. A quasi-experimental was applied on this research with a total of 30 samples that were divided into two groups. Each sample was tested using LLOYD Universal Testing Machine with 1 mm/min speed to evaluate the compressive strength. The compressive strength results were marked when the sample was broken. The results of two groups were then analyzed using t-test statistical calculation. The results of this study show that post cure treatment on hybrid composite using LED light box (194.138 MPa) was lower than dry heat treatment (227.339 MPa), which was also significantly different from statistical analysis. It can be concluded that compressive strength of LED light box was lower than dry heat post-cure treatment on the hybrid composite resin.